An ethical inquiry of support workers' experiences related to sexuality in the context of intellectual disabilities in Quebec, Canada. (22nd February 2019) - Pariseau‐Legault, Pierre; Holmes, Dave; Ouellet, Guillaume; Vallée‐Ouimet, Sandrine
Accessible summary: Support workers' attitudes towards the sexuality of people with intellectual disabilities are important. They can influence the support people with intellectual disabilities receive regarding their affective and sexual life. Six support workers talked about their personal experiences. They talked about what they found easy and difficult when helping people with intellectual disabilities express their sexual life and needs. They said that sexuality is a right, a health matter and an important need. They also said it was sometimes difficult to include sexuality in their work. They also said they often feel insecure and uncertain about how to help because sexuality is a difficult subject to talk about. They wanted to help people make their own decisions, but also wanted to protect them if needed. Abstract: Background: In the last decade, the evolution of support workers' attitudes towards the affective and sexual lives of people with intellectual disabilities has been described as increasingly positive. However, restrictive attitudes targeting affective and sexual life are still documented. Material and methods: This study aimed to explore the ethical implications of support workers' experiences concerning sexuality in the context of intellectual disabilities in everyday practice. This inquiry was guided by the following research questions: (a) In the context of intellectual disabilities, what meanings do service users' sexuality have for support workers? (b) How are those meanings translated into practice? Inspired by critical phenomenology, in‐depth individual interviews with support workers were conducted and analysed. Results: One superordinate theme (Negotiating Interventions) and three themes were identified: "Crossing Organizational Borders, " "A Duty to Act Despite Uncertainty" and "Navigating Competing and Contradictory Discourses." Conclusion: Support workers' experiences related to sexuality in the context of intellectual disabilities are influenced by how they define their role in a clinical context. This role is influenced by how affective and sexual life is included in practices, local policies and interdisciplinary work. Despite positive attitudinal changes, sexuality is still regarded as a sensitive topic capable of endangering both service users and support workers.